Kritik Sosial melalui Stilistika dan Retorika dalam Puisi Prancis: Studi Komparatif Periode Sastra Pra-1900 dan Pasca-1900 - Faizal Imansyah Rhamadhan; Dadang Sunendar; Dudung Gumilar (Faculty of Languages and Arts, Universitas Negeri Padang, 2026)
This study aims to analyze the use of stylistics and rhetoric in the representation of social criticism in pre-1900 and post-1900 French poetry. The novelty of this research lies in its theoretical integration, which explicitly combines the concepts of stylistics, Aristotelian classical rhetoric, and Fairclough's model of Critical Discourse Analysis as the primary analytical framework to uncover issues of inequality, humanity, and social reality. Employing a descriptive qualitative method, this study compares the aesthetic characteristics of both eras. Pre-1900 poetry is examined based on its emphasis on fixed forms, classical language, and tradition, whereas post-1900 poetry is analyzed through the aspects of freedom of expression, rejection of traditional conventions, subjectivity, ambiguity, and wordplay. The data sources for this research consist of ten pre-1900 poems and ten post-1900 poems. Data collection was conducted by documenting the dominant linguistic styles and their rhetorical functions in representing social criticism, with the researcher serving as the primary instrument. The results indicate that pre-1900 poetry tends to utilize symbolic and metaphorical styles with implicit rhetorical functions. Conversely, post-1900 poetry prominently features direct, repetitive, and confrontational styles. These differences demonstrate that stylistic and rhetorical tendencies in poetry reflect the aesthetic and ideological characteristics of each literary period. Theoretically, this study offers a specific contribution in the form of a new interdisciplinary approach model, proving that the integration of stylistics, classical rhetoric, and Critical Discourse Analysis is effective in distinguishing the shifting ways social criticism is represented across different periods of French literature.